Organizational capabilities in the digital era: Reframing strategic orientation - Ludovico Bullini Orlandi (Journal of Innovation & Knowledge (JIK), 2016)
The digital era is changing consistently the previous marketing scenarios and actual issues have to be addressed in order to close the capabilities gap created by digital innovations. Different authors call for theoretical and empirical contributions that cope with the issues brought out by the digitalization of marketing channels and the consequent ever increasing volume of digital data. This study develops a theoretical framework and propositions through a reframing and reconceptualization of previous theoretical constructs from managerial and marketing literature. The resulting model offers insights about organizational processes and capabilities needed to cope with the actual fast changing, but at the same time, data-rich environment.
Keywords: M1; M3; 650; Digital era; Organizational capabilities; Marketing dynamic capabilities; Knowledge process; Responsiveness; Organizational performance